THE INFLUENCE OF ATTRACTION, LOCATION, AND SERVICE QUALITY ON REVISIT INTENTION TO SESAOT RURAL TOURISM - Rahmawati, Nouria; Permadi, Lalu Adi; Rinuastuti, Baiq Handayani (Jurnal Magister Manajemen, 2021)
This study aims to determine Attraction, Location, and Service Quality influence on Revisit Intention to Sesaot Rural Tourism Area, Narmada District, West Lombok Regency, and West Nusa Tenggara. The respondents were tourists who had visited Sesaot Rural Tourism. The data collection method is a survey sample with sampling techniques using purposive sampling with a total sample of 100 people—data collection techniques using questionnaires with data collection tools using questionnaires that tested validity and reliability. The analytical technique used is multiple linear regression. The results showed that the Attraction variable does not affect Revisit Intention. As for location variables also do not affect Revisit Intention. On the other side, service quality affects Revisit Intention.